Anthropology and history: elements towars a criticism of modernity - Fuentes, Juan B.; Muñoz, Fernando (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
Our aim is to outline the sketch of a philosophy of history by establishing the relationship between two commonly recognized ways of understanding historical time, which we have designated as «annular» and «secular». Such an idea of history leads us to a criticism of the modern program of cancellation of the historical course as a final fulfilment of the project of rationalization and pacification of the world. The purpose is to show in which way that project is far from having been fulfilled and how our time is rather characterized by a singular «crisis of the anthropological elements» of history, due to a very peculiar «turbulence» taking place within the dimension of historical time, which we have characterized as «annular» or anthropological. This turbulence would be the effect of the existence of modern ways of production and consumption that are capable of ruining the fabric of enseres, which constitute what we have understood as the cultural endoskeleton of society and thus the source of opening to the world. Such a diagnostic requires, in turn, the determination of the society’s function as endoskel ton and as the source of opening to the world that we confer on objects of technique or enseres.